2019
DOI: 10.2147/jep.s209085
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Effect of Sertraline on Hemodynamic Parameters and Nitric Oxide Production in Isolated Rat Hearts Subjected to Ischemia and Reperfusion</p>

Abstract: Purpose: The aim of the study was to investigate the effect of sertraline on the rat heart during ischemia and reperfusion and to determine its effect on NO production. Materials and methods: The study was performed on isolated rat hearts. Hearts from three groups were perfused with sertraline at three different concentrations and subjected to global ischemia and reperfusion. Hearts from the other three groups were perfused with the same concentrations of sertraline but without the ischemia/reperfusion process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…A study using rat aortic rings found that calcium channels are inhibited by sertraline, causing relaxation of aortic smooth muscle, an effect that was independent of serotonergic mechanisms (Becker et al , 2004). Similarly, a recent study using isolated rat hearts to investigate ischemia and reperfusion reported that sertraline had a strong vasodilatory effect on coronary vessels (Grotthus and Szelag, 2019). Contractile responses to noradrenaline, KCl and EFS in rat isolated vas deferens was also inhibited by sertraline treatment similarly via effects on calcium channels (Kalyoncu et al , 1999).…”
Section: Discussionmentioning
confidence: 97%
“…A study using rat aortic rings found that calcium channels are inhibited by sertraline, causing relaxation of aortic smooth muscle, an effect that was independent of serotonergic mechanisms (Becker et al , 2004). Similarly, a recent study using isolated rat hearts to investigate ischemia and reperfusion reported that sertraline had a strong vasodilatory effect on coronary vessels (Grotthus and Szelag, 2019). Contractile responses to noradrenaline, KCl and EFS in rat isolated vas deferens was also inhibited by sertraline treatment similarly via effects on calcium channels (Kalyoncu et al , 1999).…”
Section: Discussionmentioning
confidence: 97%
“…Sertraline had no effect on nitric oxide levels in coronary vessels in any condition. The effects of SSRIs on the heart may be related to the blocking of voltage-gated L-type calcium channels and not the effects of serotonin reuptake [ 36 ].…”
Section: Reviewmentioning
confidence: 99%